2015
DOI: 10.1016/j.jdiacomp.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Insulin glargine compared with premixed insulin for management of insulin-naïve type 2 diabetes patients uncontrolled on oral antidiabetic drugs: the open-label, randomized GALAPAGOS study

Abstract: Glargine (±glulisine) and premix strategies resulted in similar percentages of well-controlled patients without hypoglycemia, with more patients achieving target HbA1c with premix whereas overall symptomatic hypoglycemia was less with glargine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
58
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 14 publications
2
58
0
3
Order By: Relevance
“…The lack of a comparator makes it difficult to assess the specific effect of insulin glargine. However, the improvements in glycemic control over the study period are consistent with previous randomised controlled trials performed in patients not optimally controlled with premixed insulin and who switched to insulin glargine (Inzucchi, 2015, Aschner et al, 2015. Secondly, the decision to initiate insulin glargine was not based on a planned treatment algorithm but was made at the discretion of the physician at the consultation visit.…”
Section: Discussion:-supporting
confidence: 78%
“…The lack of a comparator makes it difficult to assess the specific effect of insulin glargine. However, the improvements in glycemic control over the study period are consistent with previous randomised controlled trials performed in patients not optimally controlled with premixed insulin and who switched to insulin glargine (Inzucchi, 2015, Aschner et al, 2015. Secondly, the decision to initiate insulin glargine was not based on a planned treatment algorithm but was made at the discretion of the physician at the consultation visit.…”
Section: Discussion:-supporting
confidence: 78%
“…Aschner et al [15] compared glycaemic control in insulin-naive T2DM patients taking insulin glargine (QD with/without glulisine) versus premixed insulin (QD/BID). The primary endpoint-the percent of patients achieving an HbA 1c <7% with no symptomatic hypoglycaemia-was similarly achieved at the end of 24 weeks, demonstrating the non-inferiority of insulin glargine and rapidacting insulin versus premixed insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a more recent meta-analysis demonstrated that treatment with biphasic insulin aspart 30 (aspart/aspart protamine 30/70) once or twice daily resulted in better glycemic control in comparison with insulin glargine once daily (-0.21 %; -0.35 to -0.08) [9]. Similarly, the recently published GALAPA-GOS study demonstrated that in insulin-naive patients, premixed insulin once or twice daily reduced HbA 1c by a further 0.16 % (confidence interval 0.04 to 0.27) compared with insulin glargine with or without insulin glulisine [10]. Finally, in a subgroup analysis in insulin-naïve patients, premixed regimen had no difference with basal-bolus regimens (-0.15 %; -0.52 to 0.22) [11].…”
mentioning
confidence: 86%
“…This was corroborated in a pooled analysis of three studies comparing biphasic insulin aspart 30 twice daily with insulin glargine once daily in insulin-naïve patients (1.16 kg; -0.41 to 2.74) [9]. Similarly, body weight increase in insulin-naive patients in the GALA-PAGOS trial was comparable between those randomized to insulin glargine with or without insulin glulisine once daily and those treated with a premixed insulin regimen once or twice daily (LS mean difference -0.3 kg; p = 0.12) [10]. Likewise, in the LanScape trial, there was no difference in weight gain between basal-plus and biphasic insulin regimens (-0.44 kg; -1.12 to 0.23) in patients inadequately controlled on basal insulin and oral antidiabetic agents [12].…”
mentioning
confidence: 89%
See 1 more Smart Citation